Peran Humas Gereja Katedral Bogor Dalam Membina Hubungan Kepada Publik - Sinaga, Elisabeth Pingkan; Sinaga, Lerman (Jurnal Komunikasi Profesional, 2019)
The purpose of this research is to know roles of Cathedral Bogor’s public relations in maintaining relationship between internal and external public, the role’s obstacles and the solutions on facing the obstacles. This research found that there are five roles of PR Cathedral Bogor Church in maintaining good relationship between internal and external public. 1) role is applied a theme that already being chosen, 2) uses media communication, creates events that involves external public, and joins the Basolia (Badan Sosial Lintas Agama), 3) identifies opinion, perception and feedback from the public, 4) serves the public needs with accepting feedback, 5) defines internal and external of the organization and controls the wave of the information.Keywords: Public Relation’s roles, Maintaining Relationship.